2012
DOI: 10.1007/s00535-012-0535-x
|View full text |Cite
|
Sign up to set email alerts
|

Short-term reductions in non-protein respiratory quotient and prealbumin can be associated with the long-term deterioration of liver function after transcatheter arterial chemoembolization in patients with hepatocellular carcinoma

Abstract: Reductions in npRQ and preAlb 7 days after TACE were associated with the long-term deterioration of liver function. With our model, we were able to identify high-risk patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 35 publications
1
31
0
Order By: Relevance
“…Another possible reason is that, in the majority of cases, patients with HCC frequently underwent other treatments prior to sorafenib therapy. Popular HCC therapies may cause the deterioration of liver function, potentially leading to a decreased quality of life and the occurrence of sarcopenia in patients with HCC (37). Consistent with previous studies, the presence of sarcopenia was associated with poor PS and poor liver function in the present study (38,39).…”
Section: Discussionsupporting
confidence: 90%
“…Another possible reason is that, in the majority of cases, patients with HCC frequently underwent other treatments prior to sorafenib therapy. Popular HCC therapies may cause the deterioration of liver function, potentially leading to a decreased quality of life and the occurrence of sarcopenia in patients with HCC (37). Consistent with previous studies, the presence of sarcopenia was associated with poor PS and poor liver function in the present study (38,39).…”
Section: Discussionsupporting
confidence: 90%
“…Previous studies have shown that the supplementation of oral branched-chain amino acid (BCAA) granules improves energy metabolism in cirrhotic patients without HCC (10). In general, energy metabolism is evaluated according to the non-protein respiratory quotient (npRQ) based on indirect calorimetry (11)(12)(13). Moreover, recent studies have shown that supplementation with BCAA-enriched nutrients improves the npRQ in HCC patients after RFA (14).…”
Section: Introductionmentioning
confidence: 99%
“…The long-term deterioration of liver function after TACE can originate from the progression of energy malnutrition (Saito et al 2012a). In general, the non-protein respiratory quotient (npRQ) is the main factor used to evaluate energy metabolism on the basis of indirect calorimetry (Tajika et al 2002).…”
Section: Resultsmentioning
confidence: 99%
“…In general, the non-protein respiratory quotient (npRQ) is the main factor used to evaluate energy metabolism on the basis of indirect calorimetry (Tajika et al 2002). Short-term reduction in npRQ was found to be related to long-term liver dysfunction after TACE (Saito et al 2012a). On the other hand, no background characteristic factors that could promote the development of energy malnutrition after TACE have been identified.…”
Section: Resultsmentioning
confidence: 99%